2018
DOI: 10.1007/s00264-018-4046-0
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Bankart repair for the acute anterior shoulder dislocation: systematic review and meta-analysis

Abstract: The outcome of immediate arthroscopic repair of primary anterior shoulder dislocation is superior and encouraging with significant reduction in failure and revision rates compared to conservative treatment. Nevertheless, the failure and revision rates are statistically insignificant compared to arthroscopic reconstruction of recurrent dislocation. Hence, there is evidence to support immediate arthroscopic repair option for primary anterior shoulder dislocations over conservative treatment in young active patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 25 publications
0
29
1
Order By: Relevance
“…In 2013, Abouali et al reviewed 16 articles and 349 patients who underwent revision arthroscopic Bankart repair and reported a 12.7% rate of recurrent instability [30]. Comparatively, recurrent instability rates after arthroscopic primary Bankart repair for acute shoulder dislocation range from 7.7 to 19.6%; the revision rate was 7.1% [31]. Based on studies observed in more than ten years of follow-up after arthroscopic Bankart repair, the overall rate of recurrent instability was 31.2%, with 16.0% of patients having recurrent dislocations, and the overall revision rate was 17.0% [32].…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, Abouali et al reviewed 16 articles and 349 patients who underwent revision arthroscopic Bankart repair and reported a 12.7% rate of recurrent instability [30]. Comparatively, recurrent instability rates after arthroscopic primary Bankart repair for acute shoulder dislocation range from 7.7 to 19.6%; the revision rate was 7.1% [31]. Based on studies observed in more than ten years of follow-up after arthroscopic Bankart repair, the overall rate of recurrent instability was 31.2%, with 16.0% of patients having recurrent dislocations, and the overall revision rate was 17.0% [32].…”
Section: Discussionmentioning
confidence: 99%
“…5,9,26,35,37 Arthroscopic repair is more common, owing to superior patient-reported outcomes and range of motion postoperatively; however, lower recurrence rates are often reported with open approaches. 38 Although a 2018 systematic review by Adam et al 2 reported an average recurrence rate of 13.7% after arthroscopic Bankart repair and a revision rate of 7.1%, rates of recurrence are highly variable, with reported rates ranging from 2% 25,28,34 to 40%. 31,84…”
mentioning
confidence: 99%
“…Various factors have been associated with an increased risk of recurrent instability after Bankart repair. These include the total number of instability events before surgery, 2,34,45 placement of anchors, 54 and concomitant injuries present at surgery. 53 Kasik and Saper 33 found a considerable variation in the means of reported clinical outcomes after arthroscopic Bankart repair.…”
mentioning
confidence: 99%
“…[ 17 ] The anterior instability of shoulder joint is the result of primary dislocation, accompanied by the related diseases, for instance, the Bankart disease. [ 18 ] In the shoulder diseases, clinical results may be affected through the biopsychosocial features, patient expectations or the personality traits. No program supported by postdischarge phone is utilized for the shoulder instability.…”
Section: Discussionmentioning
confidence: 99%